ANALYSIS OF SEISMICITY AND RETURN PERIOD OF EARTHQUAKES IN SOUTH PESISIR REGENCY WEST SUMATRA PROVINCE USING THE LIKELIHOOD METHOD - Husna, Azmi Asmaul; Syafriani, Syafriani; Hamdi, Hamdi; Dwiridal, Letmi (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2024)
The South Pesisir area was one of the areas that was rocked by an earthquake on September 30, 2009. The earthquake that occurred caused damage and loss of life. Based on these conditions, the South Pesisir Regency area was identified as an earthquake-prone area. Therefore, it is necessary to research seismicity and return period in the regency. This research used the statistical likelihood method to determine the accumulated rock stress, seismcity and return period of eartquakes. The data used is earthquake data for the period 1934-2023 with a magnitude ≥4 SR and a depth of ≤300 km. The results of this research provided an overview of the seismicity and return period in the South Pesisir Regency. Seismicity was determined based on rock stress condition (b-value) and on the level seismic activity (a-value). Based on calculations showed that the a-value and b-value for the 20-year and 90-year intervals ranged between 6.16-10.9 and 0.953-2.17, respectively. Earthquakes return periods at intervals of 20 years and 90 years for the magnitude range 4.0-4.4 produced almost the same return period, namely less than one year. Meanwhile, earthquakes with magnitudes of 4.5-6 had recurrence periods ranging from 1 to 63 years.